Time-varying Nairu and real interest rates in the Euro Area - Camille Logeay; Silke Tober (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper analyses the Nairu in the Euro Area and the influence that monetary policy had on its development. Using the Kalman-filter technique we find that the Nairu has varied considerably since the early seventies. The Kalman-filter technique is applied here for the first time using explicit exogenous variables. In particular real interest rates were found to explain a quarter of the increase in the Nairu between 1980 and 1995. This indicates the possibility of a long-run non-superneutrality of monetary policy.
Keywords: E32; C32; E52; 330; Nairu; Monetary Policy; Kalman Filter; Phillips curve; Superneutrality; Natürliche Arbeitslosigkeit; Phillips-Kurve; Geldpolitik; Realzins; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten